Immune Checkpoint Inhibitors (ICI) in the Functional Cure of Hepatitis B: A Narrative Review - I Komang Wisuda Dwija Putra; I Ketut Mariadi; Gde Somayana (The Indonesian Society for Digestive Endoscopy, 2026)
Chronic hepatitis B (CHB) remains a major global health burden, largely due to the persistence of covalently closed circular DNA (cccDNA) within infected hepatocytes, which hinders complete viral eradication despite long-term antiviral therapy. In recent years, immune checkpoint inhibitors (ICIs) have emerged as a potential therapeutic strategy by restoring exhausted antiviral immune responses. This review explores the mechanisms of action of ICIs, their current application in hepatitis B virus (HBV) infection, and their potential role in achieving a functional cure. Available evidence indicates that ICIs targeting programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), and cytotoxic T-lymphocyte–associated protein 4 (CTLA-4) are capable of partially restoring HBV-specific T-cell function and reducing intrahepatic cccDNA transcriptional activity. Early-phase clinical studies have demonstrated encouraging outcomes, including declines in hepatitis B surface antigen (HBsAg) levels and occasional HBsAg loss; however, consistent achievement of a functional cure remains limited. Notably, combination strategies involving ICIs with therapeutic vaccines or nucleos(t) ide analogues appear to enhance antiviral efficacy compared with monotherapy. In conclusion, ICIs represent a promising adjunctive approach for CHB treatment and may contribute to the pursuit of a functional cure. Nevertheless, further well-designed clinical trials are required to establish their long-term safety, optimal treatment combinations, and effectiveness, particularly in HBV-endemic populations.